Technology and Music - Jane Beethoven; Rosanne Emery; Cliff Lenz (Music magic video library, 1991)
Viewers are introduced to a host of ways to make music with the help of technology - - Learn about synthesizers, samplers, MIDI, and recording techniques - - See how the famous rock group, The Hooters, works at a recording session - - Hear how sounds can be digitally processed.